Evaluación de los modos de conexión para NB-IoT - Segura Ramos, David; Khatib, Emil Jatib; Munilla-Fajardo, Jorge; Barco-Moreno, Raquel (My University, 2021)
In the 3GPP LTE Release 13, NB-IoT was standardized to provide wide-area connectivity for IoT. To optimize network signalling and power consumption, control plane (CP) and user plane (UP) optimizations were introduced. Also, to support infrequent small data transmissions, in Release 15 Early Data Transmissions (EDT) was introduced, where the data is sent during the random access procedure. Therefore, this paper analyses the latency performance of the different NB-IoT optimizations. The study, which has been carried out in NS-3, has been performed for different packet sizes. Evaluation results show that with low packet size, EDT with CP provides lower latency. However, with higher packet sizes, user plane solutions provide better latency.
Keywords: Datos - Transmisión; Radio; Modos de conexión; Industria 4.0; NB-IoT; IoT